Techniques for designing and analyzing algorithms - Stinson, Douglas R. (Douglas Robert) 1956- (CRC Press, an imprint of the Taylor & Francis Group, 2022)
"Design and analysis of algorithms can be a difficult subject for students due to its sometimes-abstract nature and its use of a wide variety of mathematical tools. Here the author, an experienced and successful textbook writer, makes the subject as straightforward as possible in an up-to-date textbook incorporating various new developments appropriate for an introductory course. This text presents the main techniques of algorithm design, namely, divide-and-conquer algorithms, greedy algorithms, dynamic programming algorithms, and backtracking. Graph algorithms are studied in detail, and a careful treatment of the theory of NP-completeness is presented. In addition, the text includes useful introductory material on mathematical background including order notation, algorithm analysis and reductions, and basic data structures. This will serve as a useful review and reference for students who have covered this material in a previous course. Features The first three chapters provide a mathematical review, basic algorithm analysis, and data structures. Detailed pseudocode descriptions of the algorithms along with illustrative algorithms are included. Proofs of correctness of algorithms are included when appropriate. The book presents a suitable amount of mathematical rigor. After reading and understanding the material in this book, students will be able to apply the basic design principles to various real-world problems that they may encounter in their future professional careers"--Provided by publisher.